2008
DOI: 10.1016/j.ecolind.2007.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Use of biotic indices in semi-enclosed coastal ecosystems and transitional waters habitats—Implications for the implementation of the European Water Framework Directive

Abstract: This study deals with the application of macrozoobenthos-based biotic indices (BI) within the frame of the implementation of the European Water Framework Directive. More precisely, this study aimed at assessing the performance of five recently developed methodologies (BI) for the assessment of ecological quality status (EcoQ) in two semi-enclosed, sheltered coastal ecosystems and in one transitional water body situated along the Western French coast, namely Marennes-Oléron Bay, Arcachon Bay, and the Seine Estu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(122 citation statements)
references
References 46 publications
(67 reference statements)
2
112
1
2
Order By: Relevance
“…They claim that amphipods associated with the common presence of macroalgae in Adriatic transitional waters are probably sufficient to increase the ecological quality of the station through the BOPA model. Pranovi et al (2007) also found that BOPA showed low discrimination in the Venice lagoon, classifying all the samples in the high category and, in the same way, Blanchet et al (2008) found the same problem, BOPA classified a large majority of stations of the French Coast as acceptable (''good" or ''high" status). Afli et al (2008) also showed that off the Tunisian coast BOPA index appeared to be somewhat severe, classifying only two stations in moderate and poor statuses.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…They claim that amphipods associated with the common presence of macroalgae in Adriatic transitional waters are probably sufficient to increase the ecological quality of the station through the BOPA model. Pranovi et al (2007) also found that BOPA showed low discrimination in the Venice lagoon, classifying all the samples in the high category and, in the same way, Blanchet et al (2008) found the same problem, BOPA classified a large majority of stations of the French Coast as acceptable (''good" or ''high" status). Afli et al (2008) also showed that off the Tunisian coast BOPA index appeared to be somewhat severe, classifying only two stations in moderate and poor statuses.…”
Section: Discussionmentioning
confidence: 77%
“…This index has already been used for monitoring the impact of pollution on different macrobenthic communities (Quintino et al, 2006;Pranovi et al, 2007;Mistri, 2007, 2008; Afli et al, 2008;Blanchet et al, 2008;Bouchet and Sauriau, 2008). However, a biotic index is unlikely to be universally (Pranovi et al, 2007;Afli et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…http://epublishing.ekt.gr | e-Publisher: EKT | Downloaded at 12/05/2018 07:03:14 | agreement was measured as 0 or 5, partial agreement as 1 or 4 and disagreement as 2 or 3 (Blanchet et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…It is also emphasized the small lists of species, especially crustaceans, included in the attribution of the scores. Another point is that this index presents some limitations when applied to estuaries and lagoons (Simboura and Zenetos, 2002;Blanchet et al, 2007).…”
Section: 4mentioning
confidence: 99%
“…Once it draws on the response of organisms to organic inputs in the ecosystem it does not detect the effects caused by other types of pollution, as for instance toxic pollution (Marín-Guirao et al, 2005). Moreover, this index presents some limitations when applied to semi-enclosed systems (Blanchet et al, 2007). 2.2.2.…”
Section: 2mentioning
confidence: 99%